The Influence of the 1997 Updated Classification Criteria for Systemic Lupus Erythematosus : Epidemiology, Disease Presentation, and Patient Management - Eilertsen, Gro Østli; Becker-Merok, Andrea; Nossent, Johannes C (The Journal of Rheumatology, 2009)
The influence of the 1997 updated classification criteria for systemic lupus erythematosus: epidemiology, disease presentation, and patient management. Eilertsen GØ, Becker-Merok A, Nossent JC. Department of Rheumatology, Medical School, University of Tromsø, 9037 Tromsø, Norway. gro.ostli.eilertsen@unn.no OBJECTIVE: The 1997 update of the American College of Rheumatology classification criteria (ACR97) for systemic lupus erythematosus (SLE) has not been validated. We determined to what extent their introduction influenced the epidemiology and clinical characteristics of the disease in northern Norway. METHODS: Annual incidence and point-prevalence rates, clinical manifestations, and outcome were determined in an inception cohort of patients with SLE in northern Norway, included between 1996 and 2006, using ACR97 criteria (97acr). These findings were compared with a cohort from the same area enrolled 1978-1995 using the 1982 revised criteria ACR82 (82acr). RESULTS: The mean annual incidence of SLE was 3.00 for cohort 97acr (n = 58) versus 2.63 for cohort 82acr (n = 81) (p = 0.5). All patients in the 97acr cohort also fulfilled the 1982 criteria; however, significantly fewer patients presented with discoid rash [odds ratio (OR) 0.31)], arthritis (OR 0.24), renal (OR 0.28) or hematological disorder (OR 0.27), and significantly more with anti-dsDNA (OR 2.57) and antiphospholipid antibodies (OR 27.9). Initial treatment with intravenous pulse methylprednisolone (OR 9.23), azathioprine (OR 6.32), and low-dose aspirin (OR 20.9) was increased in cohort 97acr. Five- (95.2%) and 10-year survival (91.9%) rates were also improved for cohort 97acr. CONCLUSION: The ACR97 criteria set has construct validity compared to the ACR82 criteria set. SLE incidence remains unchanged in northern Norway, but a significant reduction of renal disease and further improvements in survival rates occurred simultaneously with increased serological surveillance with ELISA-based assays and early immunosuppressive and anticoagulant therapy.